KAMPANYE KESADARAN DONOR DARAH MASYARAKAT KOTA MAKASSAR (STUDI STRATEGI DAKWAH HUMANIS) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
The purpose of this research is to find out how the socialization of PMI’s public relations to increases awareness of blood donors for the people of Makassar. The type of research is qualitative research. Qualitative research is research that seeks to understand how an individual sees, interprets, or describes his social world. This understanding is the result of social interaction. Understanding is the essence of qualitative research. The results showed that the lack of awareness of blood donors for the people of Makassar was caused by a lack of social awareness of the community to help other people's lives and the lack of information obtained about blood donors. As far as we know, PMI Makassar City only invites the public to blood donation events through their social media due to limited funds.